Structural design of hybrid buoyant aircraft's model for subsonic wind tunnel testing - , Anwar-Ul-Haque; Nugraha, Fauzul; Erawan, Dadang F; Asrar, Waqar; Sulaeman, Erwin (IEEE, 2017)
In subsonic wind tunnel testing, a scaled down model should be rigid enough such that due to model deformations, there is no change in the flow field. In this regard, a computational study is carried out to analyze the stress distribution and deformation of a scaled down model of a hybrid buoyant (HB) aircraft, while tested in wind tunnel test section at its maximum operational speed. Model is simulated in computational fluid dynamics (CFD) to get the pressure distribution on its surface as an input for computational engineering analysis. Model is assumed as solid model and using aluminum material for the aerodynamic surfaces. Some assumptions such as steady state, smooth wall, incompressible, isotropic material and filled solid are applied to the said model to simplify the computational case. In order to know the maximum stress and deformation of the lifting surfaces of the model, we only analyze HB aircraft at maximum angle of attack, before the stall will occur. The value of angle of attack at given maximum CL was set as HB aircraft’s model position for estimation of the deformations when being simulated using ANSYS®. A number of CFD cases were run to get the coefficient of lift versus angle of attack curve, including the value of angle of attack at maximum coefficient of lift of the wing before the stall. The maximum displacement was found at the tip of the wing and its value is 37 mm. Following any major design change of the airframe of the model, a quick numerical analysis is recommended to determine if there any significant alterations to the original model.